Fabrication of magnetic Fe3O4/MnO2/TiO2/polypyrrole heterostructure for efficient adsorption of Mn7+ from aqueous solution. Issue 21 (12th February 2022) - Wang, Wenjiao; Zheng, Mingming; Ren, Jiajia; Ma, Mingliang; Yin, Xunqian; Li, Tingxi; Ma, Yong
Abstract: Magnetic Fe3 O4 /MnO2 /TiO2 /polypyrrole (PPy) heterostructure as adsorbent for adsorbing Mn 7+ was synthesized by combining hydrothermal method and chemical oxidation method. The heterostructure was characterized by field‐emission scanning electron microscope, Fourier transform infrared spectroscopy, X‐ray diffraction, and vibrating sample magnetometer. Its saturation magnetization is 18.88 emu/g, so it is easy to separate it from the solution. The feasibility of Fe3 O4 /MnO2 /TiO2 /PPy heterostructure to remove Mn 7+ was researched in detail. It is found that the optimal pH is 2. The initial adsorption rate can reach 4.60 mg/g min. At 288.15 K, the maximum equilibrium adsorption capacity is 202.8 mg/g. Adsorption kinetics follows a pseudo second order model, as well as is determined by through membrane diffusion processes. The Langmuir isotherm model is used to describe the adsorption isotherm behavior. Besides, thermodynamic parameters indicate spontaneous adsorption behavior, and entropy of the endothermic reaction increases. Finally, the cycle test results show that the adsorbent has better cycle performance, displaying broad application prospects. Abstract : Magnetic Fe3 O4 /MnO2 /TiO2 /PPy heterostructure is successfully fabricated by layer‐by‐layer coating with good acid resistance, which can achieve rapid adsorption and separation of Mn 7+ from water.